'At this [adherence] club, we are a family now': A realist theory-testing case study of the antiretroviral treatment adherence club, South Africa - Ferdinand C. Mukumbang; Brian van Wyk; Sara Van Belle; Bruno Marchal (AOSIS, 2019)
Background: An estimated 7.9 million people were living with HIV in South Africa in 2017, with 63.3% of them remaining in antiretroviral therapy (ART) care and 62.9% accessing ART. Poor retention in care and suboptimal adherence to ART undermine the successful efforts of initiating people living with HIV on ART. To address these challenges, the antiretroviral adherence club intervention was designed to streamline ART services to 'stable' patients. Nevertheless, it is poorly understood exactly how and why and under what health system conditions the adherence club intervention works. Objectives: The aim of this study was to test a theory on how and why the adherence club intervention works and in what health system context(s) in a primary healthcare facility in the Western Cape Province. Method: Within the realist evaluation framework, we applied a confirmatory theory-testing case study approach. Kaplan-Meier descriptions were used to estimate the rates of dropout from the adherence club intervention and virological failure as the principal outcomes of the adherence club intervention. Qualitative interviews and non-participant observations were used to explore the context and identify the mechanisms that perpetuate the observed outcomes or behaviours of the actors. Following the retroduction logic of making inferences, we configured information obtained from quantitative and qualitative approaches using the intervention-context-actor-mechanism-outcome heuristic tool to formulate generative theories. Results: We confirmed that patients on ART in adherence clubs will continue to adhere to their medication and remain in care because their self-efficacy is improved; they are motivated or are being nudged. Conclusion: A theory-based understanding provides valuable lessons towards the adaptive implementation of the adherence club intervention.